The Determining Success of Polyculture Caulerpa sp and Litopenaeus vannamei using AHP Analysis - Andhini, Nadia; Muna, Zakyatul; Fazri, Kurniawan; Khobir, Muhammad Latiful; Fuah, Ricky Winrison; Akbar, Muhammad Wahyu; Achiar, Anshari Luthfi Maulana (Institut Teknologi Sepuluh Nopember, 2024)
The Polyculture Caulerpa sp and Litopenaeus vannamei can reduce the risk of ecological impacts, increase shrimp growth, survival, production, increase shrimp resistance to disease, and maintain optimal water quality. Analytical Hierarchy Process (AHP) begins by determining the priority between water quality, growth rate, and harvest yields as more optimal parameters for the success of a polyculture. The measure of success is determined based on the results of expert assessments of polyculture and cultivation that produce more optimal water quality (temperature, pH, brightness, salinity, and dissolved oxygen), growth rates, and harvest yields. The results of the overall AHP analysis, which determined the success of Caulerpa sp and Litopenaeus vannamei polyculture based on expert assessments, showed a good level of consistency. The results show that water quality is a priority parameter in the success of Caulerpa sp and Litopenaeus vannamei polyculture with a weight of 0.597, followed by a growth rate of 0.297 and a harvest yield of 0.106. The analysis of priority water quality indicators for the success of polyculture is dissolved oxygen with a weight of 0.514, followed by pH of 0.246, salinity of 0.119, temperature of 0.079, and brightness of 0.042. Based on the results of experts of the combined weight comparison, polyculture is more optimal than cultivation, with a considerable comparison weight of 0.678 and 0.322, measuring the success of Caulerpa sp and Litopenaeus vannamei polyculture.